2022
DOI: 10.1111/fwb.13889
|View full text |Cite
|
Sign up to set email alerts
|

Trophic transfer of lipids and fatty acids across habitats in tropical river food webs

Abstract: 1. Polyunsaturated fatty acids (PUFA) are essential components of cell membranes and reproductive and sensory organs in vertebrates and are largely acquired through their diets. Accordingly, identification of the dietary sources of PUFA is an important consideration in food web studies.2. We collected fish, macroinvertebrates (aquatic and terrestrial), and plants (aquatic and terrestrial) from floodplain and river channel habitats in a tropical river catchment in northern Australia, to identify food sources an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 70 publications
0
3
0
Order By: Relevance
“…In contrast to invertebrates that selectively retained all their PUFA from the diet, substantial levels of fish-DHA were produced endogenously by both fish groups (Salmonids and European bullhead) as indicated by their 13 C-depleted liver-DHA. Previous research demonstrated that DHA is abundant in all fish organs but is virtually absent in most stream invertebrates (Ebm et al, 2021;Guo et al, 2017;O'Mara et al, 2022). To overcome DHA-deficiency, dietary precursor-PUFA (i.e., ALA, SDA, or EPA) are transformed in serial desaturation and elongation steps inducing isotopic fractionation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast to invertebrates that selectively retained all their PUFA from the diet, substantial levels of fish-DHA were produced endogenously by both fish groups (Salmonids and European bullhead) as indicated by their 13 C-depleted liver-DHA. Previous research demonstrated that DHA is abundant in all fish organs but is virtually absent in most stream invertebrates (Ebm et al, 2021;Guo et al, 2017;O'Mara et al, 2022). To overcome DHA-deficiency, dietary precursor-PUFA (i.e., ALA, SDA, or EPA) are transformed in serial desaturation and elongation steps inducing isotopic fractionation.…”
Section: Discussionmentioning
confidence: 99%
“…Stream biota obtain fatty acids (FA) from allochthonous (terrestrial) and autochthonous (e.g., algae or mosses) sources, yet retain FA profiles that differ from either dietary source (Ebm et al, 2021; Guo et al, 2017; O’Mara et al, 2022). Whether this mismatch between consumers and their food sources is due to selective retention and/or endogenous FA conversion is subject of ongoing research (Fujibayashi et al, 2019; Scharnweber et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation